Metal-involving halogen bond Ar-I [dPt] in a platinum acetylacetonate complex - Rozhkov, Anton V; Ivanov, Daniil M; Novikov, Alexander S; Ananyev, Ivan V; Bokach, Nadezhda A; Kukushkin, Vadim Yu (CrystEngComm, 2020)
A combined XRD and theoretical study for two adducts, [Pt(acac) 2 ]·2(1,3,5-FIB) and [Pd(acac) 2 ]·1,3,5-FIB (Hacac = acetylacetone; 1,3,5-FIB = 1,3,5-triiiodotrifluorobenzene), reveals that differences in the type formed halogen bond (XB) depend on the identity of the metal center. Only [Pt(acac) 2 ] forms rare two-center metal-involving XB Ar-I [d z 2 Pt II ] (where the positively charged Pt II center acts as a nucleophile toward an iodine σ-hole), while three-center bifurcated XB I η 2 (O,O) was detected in both adducts. The observed linkage Ar-I [d z 2 Pt II ] provides an experimental argument favoring the previously established (by a kinetic study) XB-formation step upon oxidative addition of I 2 to [Pt(acac) 2 ]. The variable temperature XRD study of [Pt(acac) 2 ]·2(1,3,5-FIB) (100-300 K; five XRD experiments) demonstrates that the I Pt and I O contacts weaken simultaneously on heating that allows the consideration of the Pt1-O2 bond as an integrated XB acceptor. Appropriate DFT calculations (M06/DZP-DKH level of theory) performed by single-point "quasi-solid state" calculations with topological analysis of the electron density distribution within the framework of the Bader theory (QTAIM method), confirmed the existence of the two-center metal-involving XB I Pt in the structure of [Pt(acac) 2 ]·2(1,3,5-FIB) and three-center I η 2 (O,O) bifurcated XBs for both adducts. All these interactions exhibit a non-covalent nature with estimated energies in the range of 2.1-4.3 kcal mol −1 . The observed and confirmed theoretically metal-involving halogen bond Ar-I [d z 2 Pt II ] provides experimental evidence favoring a XB formation step upon oxidative addition of ArI to Pt II .